Effects of food abundance and early clutch predation on reproductive timing in a high Arctic shorebird exposed to advancements in arthropod abundance. Issue 20 (23rd September 2016) - Reneerkens, Jeroen; Schmidt, Niels Martin; Gilg, Olivier; Hansen, Jannik; Hansen, Lars Holst; Moreau, Jérôme; Piersma, Theunis
Summary: Climate change may influence the phenology of organisms unequally across trophic levels and thus lead to phenological mismatches between predators and prey. In cases where prey availability peaks before reproducing predators reach maximal prey demand, any negative fitness consequences would selectively favor resynchronization by earlier starts of the reproductive activities of the predators. At a study site in northeast Greenland, over a period of 17 years, the median emergence of the invertebrate prey of Sanderling Calidris alba advanced with 1.27 days per year. Yet, over the same period Sanderling did not advance hatching date. Thus, Sanderlings increasingly hatched after their prey was maximally abundant. Surprisingly, the phenological mismatches did not affect chick growth, but the interaction of the annual width and height of the peak in food abundance did. Chicks grew especially better in years when the food peak was broad. Sanderling clutches were most likely to be depredated early in the season, which should delay reproduction. We propose that high early clutch predation may favor a later reproductive timing. Additionally, our data suggest that in most years food was still abundant after the median date of emergence, which may explain why Sanderlings did not advance breeding along with the advances in arthropod phenology. Abstract : Due to climate change‐induced changes in phenology, high arctic breeding sanderling chicks now hatch after the peak of their arthropod food resource. This phenological mismatch did however not negatively affect chick growth because food was still plentiful after the peak. Early predation risk of clutches may further explain why Sanderlings did not advance their breeding phenology.